Assessment and comparison of quality of life and sexual function after adjuvant therapy in post-mastectomy breast carcinoma: A prospective study - Bidisha Bandyopadhyay; Atanu Basu; Anjan Bera; Shilpi Adhikary; Debojyoti Manna; Doli Mridha; Debasmita Chakrabarti (Asian Journal of Medical Sciences, 2023)
Background: Quality of life (QoL) is an important measure in the evaluation of health, physical condition, and the effects of treatment and continues to gain importance. Health-related QoL gives information about the patient’s experiences (physical and psychological) related to the disease and the applied treatments, as well as the potential prognosis. It is known that breast surgery and its combination with chemotherapy (CT) and radiation therapy causes negative changes in the patient’s psychosocial well-being and QoL. Aims and Objectives: To study the QoL and sexual function in female breast carcinoma patients who received adjuvant CT and radiation therapy after mastectomy. Materials and Methods: This was a single institutional prospective study carried out in the Department of Radiotherapy, RG Kar Medical College and Hospital, Kolkata. From January 2017 to December 2019, according to inclusion and exclusion criteria, a total of 64 histologically proven breast carcinoma patients were included in this prospective study. Results: On symptom scale analysis, it has been noted that all the symptoms increased after receiving CT and reached their highest after the 6th cycle of CT, then improved after radiation and further improved at 6 months follow-up, except for the breast symptoms, which decreased after the 6th cycle of CT, increased immediately post-RT, and then again decreased at 6 months follow-up. Conclusion: Treatment with CT and radiation therapy significantly affects QoL, psychosexual function, and physical problems.